How is chlorine activation affected by the composition of Polar Stratospheric Clouds and background aerosol particles? - Wohltmann, Ingo; Lehmann, Ralph; Rex, Markus; Wegner, Tobias; Müller, Rolf; Manney, Gloria L.; Santee, Michelle L. (2013)
We investigate how important details of the microphysics of Polar Stratospheric Clouds (PSCs) and background aerosol particles are for the representation of polar ozone loss in chemistry transport models. For this purpose, the Lagrangian Chemistry and Transport Model ATLAS was applied to simulate the stratospheric chemistry in the Arctic winter 2009/2010. After a validation of the model results against measurements by the satelliteborne Microwave Limb Sounder (MLS), a number of sensitivity runs were performed. Thus, the efficiency of chlorine activation on different types of liquid aerosols versus activation on nitric acid trihydrate (NAT) clouds was explored. Moreover, the effects of particle composition and denitrification on ozone loss were analysed. It is shown that even large changes in the underlying assumptions regarding detailed activation surfaces have only a small impact on the modelled ozone loss. Differences in column ozone between the various sensitivity runs remain below 10% at the end of the winter. Chlorine activation on liquid aerosols alone is able to explain the observed magnitude and morphology of the mixing ratios of active chlorine, reservoir gases and ozone. This is even true for cold binary aerosols (no uptake of HNO3 from the gas-phase allowed in the model). This demonstrates that the heterogeneous chlorine activation in the polar stratosphere is dominated by the temperature dependence of the heterogeneous reaction rate constants rather than by the composition of the solid or liquid aerosol particles.